BATAS KEBEBASAN EKSISTENSIAL PEREMPUAN: ANALISIS LE DEUXIÈME SEXE DALAM CERPEN KISAH SIE SIE - Naeluzzahronnovi; Imas Juidah; Agus Nasihin (Universitas Hamzanwadi, 2026)
This study describes Simone de Beauvoir’s Le Deuxième Sexe concept in the character of Sie Sie in Tere Liye's short story “Kisah Sie Sie”. It focuses on the representation of women as the other, forms of immanence, transcendence, and women's existence within patriarchal culture. Employing a descriptive qualitative approach with existentialist feminist theory, narrative data were collected through documentation and note-taking from the novel Sepotong Hati yang Baru. Data analysis used heuristic and hermeneutic reading methods. The findings reveal that Sie Sie experiences subordination and objectification as the other within patriarchal structures and domestic confinement (immanence). However, she demonstrates transcendence through sacrifice, labor, and decision-making courage. This study shows that women’s freedom in literary works is portrayed as an existential struggle to preserve identity.